2017
DOI: 10.1002/ece3.3340
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, population structure, and traditional culture of Camellia reticulata

Abstract: Camellia reticulata is an arbor tree that has been cultivated in southwestern China by various sociolinguistic groups for esthetic purposes as well as to derive an edible seed oil. This study examined the influence of management, socio‐economic factors, and religion on the genetic diversity patterns of Camellia reticulata utilizing a combination of ethnobotanical and molecular genetic approaches. Semi‐structured interviews and key informant interviews were carried out with local communities in China's Yunnan P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
2
7
3
Order By: Relevance
“…Moreover, without grouping included in the AMOVA, the wild populations of P. polyphylla var. yunnanensis showed relatively low genetic differentiation (Φ ST = 18.83%) compared with that detected in previous studies of F. cirrhosa D. Don (Zhang et al, ) and Camellia reticulata (Xin et al, ), as well as statistical data (Nybom, ). This revealed that enough gene flow among wild populations might have occurred to have effectively prevented the aggravating of among‐population genetic differentiation.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Moreover, without grouping included in the AMOVA, the wild populations of P. polyphylla var. yunnanensis showed relatively low genetic differentiation (Φ ST = 18.83%) compared with that detected in previous studies of F. cirrhosa D. Don (Zhang et al, ) and Camellia reticulata (Xin et al, ), as well as statistical data (Nybom, ). This revealed that enough gene flow among wild populations might have occurred to have effectively prevented the aggravating of among‐population genetic differentiation.…”
Section: Discussioncontrasting
confidence: 58%
“…Moreover, without grouping included in the AMOVA, the wild populations of P. polyphylla var. yunnanensis showed relatively low genetic differentiation (Φ ST = 18.83%) compared with that detected in previous studies of F. cirrhosa D. Don and Camellia reticulata (Xin et al, 2017), as well as statistical data (Nybom, 2004).…”
Section: Spatial Genetic Structure Of Wild and The Cultivated Populcontrasting
confidence: 57%
“…CL-40 planted in Fujian Longyang showed the highest content of squalene 90.3 mg/100 g , while wild type planted in Jiangxi Ganzhou showed the lowest content 5.2 mg/100 g . In previous studies, C. reticulata showed relatively high genetic diversity 34 . Lanosterol and ergosterol as mainly found in animal and fungi were detected in COSOs.…”
Section: Sterol and Squalene Compositionmentioning
confidence: 84%
“…This alarming situation necessitates an in‐depth understanding of the current status of the genetic diversity of the species. Studies have been conducted on the genetic diversity of C. reticulata via inter‐simple sequence repeat markers, chloroplast microsatellites, and amplified fragment length polymorphisms (Wang and Ruan, ; Tong et al., ; Yao et al., ; Xin et al., ). Yao et al.…”
mentioning
confidence: 99%